Eating Disorders During Gestation: Implications for Mother's Health, Fetal Outcomes, and Epigenetic Changes - Sebastiani, Giorgia; Andreu-Fernández, Vicente; Herranz Barbero, Ana; Aldecoa-Bilbao, Victoria; Miracle, Xavier; Meler Barrabes, Eva; Balada Ibañez, Arantxa; Astals-Vizcaino, Marta; Ferrero-Martínez, Silvia; Gómez-Roig, María Dolores; García-Algar, Oscar (Frontiers in Pediatrics, 2020)
Introduction: Eating disorders (EDs) have increased globally in women of childbearing age, related to the concern for body shape promoted in industrialized countries. Pregnancy may exacerbate a previous ED or conversely may be a chance for improving eating patterns due to the mother's concern for the unborn baby. EDs may impact pregnancy evolution and increase the risk of adverse outcomes such as miscarriage, preterm delivery, poor fetal growth, or malformations, but the knowledge on this topic is limited. Methods: We performed a systematic review of studies on humans in order to clarify the mechanisms underpinning the adverse pregnancy outcomes in patients with EDs. Results: Although unfavorable fetal development could be multifactorial, maternal malnutrition, altered hormonal pathways, low pre-pregnancy body mass index, and poor gestational weight gain, combined with maternal psychopathology and stress, may impair the evolution of pregnancy. Environmental factors such as malnutrition or substance of abuse may also induce epigenetic changes in the fetal epigenome, which mark lifelong health concerns in offspring. Conclusions: The precocious detection of dysfunctional eating behaviors in the pre-pregnancy period and an early multidisciplinary approach comprised of nutritional support, psychotherapeutic techniques, and the use of psychotropics if necessary, would prevent lifelong morbidity for both mother and fetus. Further prospective studies with large sample sizes are needed in order to design a structured intervention during every stage of pregnancy and in the postpartum period.